Pengaruh Media Pembelajaran Monopoli Terhadap Hasil Belajar PPKn Siswa Materi Pahlawanku Kelas IV SD Negeri Maulafa Kota Kupang - Elagetrida Seri; Kristina E. Noya Nahak; Heryon Bernard Mbuik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Monopoly learning media plays a crucial role in learning activities. It is hoped that teachers and students at Maulafa Elementary School in Kupang City can utilize this Monopoly learning media to enhance their knowledge and enhance their learning outcomes in the Civics (PPKn) subject,